On a general theoretical foundation for endocrinology. (March 2019) - van den Berg, Hugo A
Hormones are messenger molecules that distribute across all tissues and thus operate on the whole-organism level. Moreover, a given hormone typically affects a number of different biological processes. As such, hormones coordinate concerted cooperation between the cells and tissues of an organism, a phenomenon that has been termed 'organismal harmony'. Furthermore, a concept that has recently been gaining traction is that hormones mediate or represent life history trade-offs, which are ultimately moulded by evolutionary pressures. Here, this concept is extended to include all 'decisions' or 'choices' that are made at the organismal level. A formal framework is sketched to explore the proposition that organismal biology, together with the 'fitness landscape', suffices in principle to determine minimalistic dynamics of the endocrine system.